Going beyond dyadic consultation relationships: information exchange in multi-step participation procedures. (6th August 2018) - Fink, Simon; Ruffing, Eva
Abstract: For decades, political scientists have observed the diffusion of complex governance arrangements including public participation procedures to ameliorate the democratic deficit inherent in these often-opaque structures. This article asks how the information provided in consultation statements is used by the consulting actors. To account for the multi-step character, the article combines exchange theory with a principal-agent approach, acknowledging that several actors in a delegation chain might be interested in the provided information. We use a typical case of a multi-step procedure – participation in German grid development – to test both theories. Neither the private firms nor the regulator use information provided in their own consultations, contradicting exchange theory. But the regulator considers ecological submissions made in the firms' consultation, as the principal-agent approach suggests. Thus, a principal-agent approach allows us to find influence of consultation statements that exchange theory cannot detect.